On theocratic criminal law: the rule of religion and punishment in Iran - Khodadadi, Bahman (Oxford scholarship online, 2024)
'On Theocratic Criminal Law' explores the roots and structures of the criminal law system of the world's most prominent constitutional theocracy, the Islamic Republic of Iran. The book offers a critical analysis of the way criminal law functions as the centrepiece of this theocratic mode of political domination.